Frontline Science: Anti-PD-L1 protects against infection with common bacterial pathogens after burn injury. Issue 1 (21st December 2017) - Patil, Naeem K; Luan, Liming; Bohannon, Julia K; Hernandez, Antonio; Guo, Yin; Sherwood, Edward R
Abstract: Burn patients are susceptible to infections due, in part, to immune dysfunction. Upregulation of programmed death-1 (PD-1) receptor on T cells and programmed cell death ligand-1 (PD-L1) on myeloid cells contribute to immune dysfunction in nonburn-related sepsis. We hypothesized that PD-1/PDL1 interactions contribute to immune dysfunction after burn injury. To determine the impact of burn injury and infection on PD-L1, PD-1 and costimulatory receptor expression by leukocytes and its relationship to T cell functions. The efficacy of anti-PD-L1 antibody was evaluated in a clinically relevant mouse model of burn injury and bacterial infection. Mice underwent 35% scald burn followed by Pseudomonas aeruginosa or Staphylococcus aureus infection on day 4 postburn. Anti-PD-L1 was administered on day 3 postburn. Numbers and phenotype of leukocytes, plasma cytokine concentrations, bacterial clearance, organ injury, and survival were assessed. Burn injury and infection with P. aeruginosa caused a significant upregulation of PD-L1 on myeloid cells, along with a decrease in T cell numbers and function, significant multiorgan injury, and decreased survival. Treatment with anti-PD-L1 antibody improved bacterial clearance, reduced organ injury, and enhanced survival during Pseudomonas burn wound infection. Furthermore, anti-PD-L1 effectively protected against multiorgan injury, and improved bacterial clearance and survival following systemic S. aureus infection after burn injury. Blockade of PD-1/PD-L1 interactions might represent a viable treatment to improve outcomes among critically ill burn-injured subjects and increased leukocyte PD-L1 expression could serve as a valuable biomarker to select appropriate patients for such treatment.